Matching‐adjusted comparison of oral corticosteroid reduction in asthma: Systematic review of biologics. Issue 4 (20th March 2020) - Bourdin, Arnaud; Husereau, Don; Molinari, Nicolas; Golam, Sarowar; Siddiqui, Mohd Kashif; Lindner, Leandro; Xu, Xiao
Abstract: Background: Oral corticosteroid (OCS) treatment for severe asthma is associated with substantial disease burden. Thus, OCS dosage reduction is desirable. Relative efficacy of biologics in reducing OCS treatment for severe, uncontrolled asthma is not fully characterized. Objective: We performed a matching‐adjusted indirect comparison (MAIC) to assess the relative effects on OCS treatment reduction of three biologic asthma treatments. Methods: In MAIC of benralizumab vs. mepolizumab and vs. dupilumab, patient‐level data from the Phase III benralizumab OCS‐sparing trial, ZONDA, were weighted to match treatment effect–modifying patient characteristics in comparator trials. Results: After matching adjustment, mean difference between benralizumab and mepolizumab for OCS reduction was 6.08% (95% CI −22.22‐34.38; P  = .67) by week 24, and odds ratio of OCS elimination was 2.32 (95% CI 0.48‐11.15; P  = .29). A trend in annual asthma exacerbation rate reduction favouring benralizumab over mepolizumab was observed, although it was not statistically significant (rate ratio [RR] = 0.56 [95% CI 0.28‐1.13; P  = .11]). Mean difference between benralizumab and dupilumab for OCS reduction was −0.71% (95% CI −20.56‐19.15; P  = .94), and odds ratio of OCS elimination was 2.26 (95% CI 0.52‐9.84; P  = .28). A non‐significant trend in annual asthma exacerbation rate reduction favouring benralizumab over dupilumab was observed (RR = 0.50 [95% CI 0.20‐1.28; P  = .15]). Effective sample size was 49% (72 vs. 148) and 25% (36 vs. 142) of original sample size for MAIC of benralizumab vs. mepolizumab and benralizumab vs. dupilumab, respectively. Conclusions and Clinical Relevance: Following patient baseline characteristics matching across clinical trials, benralizumab demonstrated efficacy comparable to mepolizumab and dupilumab for OCS dosage reduction, OCS elimination, and annual exacerbation rate reduction. Comparatively low effective sample sizes indicated substantial differences for patient populations between ZONDA and mepolizumab and dupilumab trials.